Indonesianizing Islamic Law: The Social Construction of Tengku Muhammad Hasbi ash-Shiddieqy’s Fikih Indonesia - Pradana Boy Zulian; Noviandy Noviandy; Cut Siti Maisyarah (Program Pascasarjana IAIN Langsa, 2026)
This study employs a qualitative library research method to examine the social construction of Tengku Muhammad Hasbi ash-Shiddieqy’s concept of fikih indonesia. Using Karl Mannheim’s sociology of knowledge as a perspective, this article argues that ash-Shiddieqy’s Islamic legal thought is not constructed out of emptiness. Rather, it is conditioned by social contexts such as social changes and dynamics as well as the need for Islamic law to adapt with the transformation within society. From the sociology of knowledge point of view, Fikih Indonesia can be viewed as a form of knowledge. As a knowledge, it is a result of dialectical relationship of many elements which includes the fundamental norms, thinkers as the subject or producers of knowledge, and social settings. Through his idea on Fikih Indonesia, ash-Shiddieqy sought to develop a concept of Islamic jurisprudence that accords Indonesian values. Such an idea originates from his critical reflection on classical Islamic jurisprudence thoughts are which he saw as heavily influenced by Middle Eastern orientation. Consequently, they are often irrelevant to the context of Indonesian society whose values, characteristics, and tendencies differ from those of Middle Eastern societies. Therefore, developing a system of Islamic jurisprudence based on the context of Indonesian society will ensure the relevance and applicability of Islamic law in the local context.. From an Islamic legal perspective, ash-Shiddieqy’s thought is one manifestation of the dialectic relationship between universality and particularity in Islamic law which is clearly underline the complex process of knowledge construction. Ash-Shiddieqy’s Fikih Indonesia is obviously an excellent model of this dialectical nature of Islamic law, and highly relevant in a time when the Arabization of Islam showing its growing trend in Indonesia